Transformatywny potencjał mediacji w sprawach rodzinnych - Zienkiewicz, Adam (Studia Prawnoustrojowe, 2019)
The main aim of the article is to draw attention to the transformative potential of mediation that can be used especially when resolving family disputes. At the beginning, the considerations focus on presenting the author’s understanding of the basic concepts of „mediation” and „personal transformation” that shape the understanding of the transformative potential of mediation. Various mediation goals are then identified and goals were set, the implementation of which can significantly realize the transformative potential of mediation. The third part of the article presents the most important assumptions of the transformative strategy of mediation. The conclusion summarises the transformative potential of mediation in the context of selected aspects of family disputes, especially between divorced spouses.